Langkah Hukum dalam Mendukung Proses Pemulihan Aset Perbankan BUMN Pasca Kasus Korupsi - Latifansyah, Muhammad Anzar; Rifai, Anis; Sadino, Sadino (Al-Ishlah: Jurnal Ilmiah Hukum, 2024)
This study aims to identify obstacles and formulate strategic measures to optimize asset recovery in the State-Owned Enterprises Banking sector post-corruption cases. This research employs a normative legal research method with a comparative approach, where the collected legal materials are analyzed qualitatively to describe the problems and answer the research objectives. The results show that asset recovery faces multidimensional challenges, including weaknesses in the legal framework, limitations in the capacity and integrity of law enforcement officers, lack of facilities and infrastructure, and efforts by the accused to avoid asset recovery. Optimizing asset recovery requires a comprehensive strategy encompassing the enactment of the Bill on Criminal Asset Forfeiture, strengthening the legal and institutional framework, enhancing the capacity and integrity of law enforcement, improving facilities and infrastructure, optimizing the civil route, and strengthening international cooperation. Therefore, it is recommended that the Government, Directors of State-Owned Enterprises Banking, the Asset Recovery Center, and law enforcement agencies undertake various optimization efforts, such as accelerating the enactment of the Bill on Criminal Asset Forfeiture, increasing the budget, strengthening corruption prevention systems, enhancing the competence of law enforcement officers, and strengthening international cooperation. Furthermore, the Public Prosecutor is expected to maximize the use of Article 18 of Law Number 31 of 1999 in indictments, enabling judges to issue optimal rulings for asset recovery in the State-Owned Enterprises Banking sector post-corruption cases.